Plato - "Gosling, J.C.B" (London, 2001)
The terms of reference of this book ensure that it will be an irritant to scholars. It is intended as a critical discussion of some of Plato's central philosophical these. In order to get enough of what I wished to discuss on the table I have had to curtail the scholarly discussion, though I have tried to supply enough to avoid instant dismissal. this is not done from any contempt for scholarship. Far from it, The prime purpose, however, has been to extract some these which can plausibly, and in my view truly, be attributed to Plato, which it is of some philosophical interest to discuss.
Keywords: Plato:Philosophy-Plato